INTENTION TO ADOPT: USING OF BARCODE SYSTEM TO REDUCE HEALTH SERVICE ERRORS - Didik Setyawan; Intatik Laelatul Makhfiroh; Finisha Mahaestri Noor (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to examine the factors driving the intention to adopt an information system through the use of patient barcode system at a hospital in Surakarta. This study is necessary to explore the variables forming the information system adoption intention in order to improve the performance of hospital medical personnel. Survey method and questionnaire were applied in data collection. The data were collected using a probability sampling technique resulting in a number of 100 questionnaires to be processed. SPSS was used to test the instrument of the study, while SEM using AMOS method was applied to test hypotheses. The results showed that to be able to increase the confidence of user to form the intention to adopt barcode systems in hospitals is influenced by the condition of the facility not because of management pressure and social pressure. Intention to Adopt Information System, Trust, Facility Condition, Managerial Pressure, Social Pressure, Barcode System.